1993
DOI: 10.1136/jcp.46.11.1055
|View full text |Cite
|
Sign up to set email alerts
|

Plasma coenzyme Q (ubiquinone) concentrations in patients treated with simvastatin.

Abstract: Plasma coenzyme Q (CoQ) was measured in 20 hyperlipidaemic patients treated with diet and simvastatin (an inhibitor of 3-hydroxy-3-methylglutaryl coenzyme A (HMG CoA) reductase); 22 hyperlipidaemic patients treated with diet with alone; and 20 normal controls. MethodsThree groups of subjects were studied: (A) 20 patients (12 men, eight women, aged 55 (SD 8 9) years; five smokers, five with hypertension, and 11 with coronary heart disease) treated with simvastatin and a fat modified diet; (B) 22 patients (nine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(47 citation statements)
references
References 8 publications
0
45
0
2
Order By: Relevance
“…In patients with ischemic cardiomyopathy (40% with diabetes), atorvastatin (10mg/day) significantly improved post-ischemic FABF, but this effect was blunted by the co-administration of vitamin E (400 IU/day) [231]. Given the potential for statins to inhibit the cellular synthesis of plasma CoQ 10 , a by-product of isoprenoid metabolism, their full benefit on improving endothelial function may be blunted [232,233]. In a randomized, double-blind, crossover study, CoQ 10 supplementation significantly improved brachial artery FMD in statin-treated T2D patients with LDLcholesterol <2.5mmol/l and ED [234].…”
Section: Combination Therapiesmentioning
confidence: 99%
“…In patients with ischemic cardiomyopathy (40% with diabetes), atorvastatin (10mg/day) significantly improved post-ischemic FABF, but this effect was blunted by the co-administration of vitamin E (400 IU/day) [231]. Given the potential for statins to inhibit the cellular synthesis of plasma CoQ 10 , a by-product of isoprenoid metabolism, their full benefit on improving endothelial function may be blunted [232,233]. In a randomized, double-blind, crossover study, CoQ 10 supplementation significantly improved brachial artery FMD in statin-treated T2D patients with LDLcholesterol <2.5mmol/l and ED [234].…”
Section: Combination Therapiesmentioning
confidence: 99%
“…Ubiquinone fibrates was associated with low ubiquinone concentrations. Whether statins lower serum ubiquinone indeserum level was significantly higher in Group 3 (untreated hypercholesterolaemic patients) than in normopendently of LDL cholesterol lowering has been debated [13,15,26 ]. In this study, we found that the molar cholesterolaemic controls (P<0.05).…”
Section: Introductionmentioning
confidence: 99%
“…Statins inhibit synthesis of mevalonate, a precursor of adverse effects of statins are muscular and include elevation of serum creatine kinase, sometimes associated both cholesterol and ubiquinone. Some studies have documented a decrease of serum levels of ubiquinone in with myalgia, rhabdomyolysis, and rarely, cases of patients receiving statins [12][13][14][15], and it is debated Study design whether or not the decrease of ubiquinone level parallels that of cholesterol level [13,15]. Ubiquinone (Coenzyme All patients participating in the study had a clinical and neurological examination, including assessment of mus-Q10) is a key-coenzyme of the mitochondrial respiratory chain [16 ], and a drug-induced decrease of ubiquinone cular strength.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, plasma levels of CoQ10 did not correlate with urinary 8-iso-PGF2α before and after ATO therapy, suggesting that plasma CoQ10 levels might not represent levels of oxidative stress in patients with coronary artery disease. Effects of ATO on CoQ10 levels: Previous studies [10][11][12] have shown that statins reduce plasma levels of CoQ10, although another study 16) reported no reduction in plasma CoQ10 levels by statins. In the present study, ATO reduced plasma levels of CoQ10 and the reduction was greater in patients with a greater reduction in cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…8,9) Statins inhibit the synthesis of mevalonate, thereby reducing plasma levels of ubiquinone. [10][11][12] Ubiquinone, ie, coenzyme Q10 (CoQ10), is a coenzyme for mitochondrial enzyme complexes involved in oxidative phosphorylation in the production of ATP. Another property of CoQ10 involves its antioxidant function.…”
mentioning
confidence: 99%